2021
DOI: 10.14258/jcprm.2021028315
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Biological Activity of Metabolites of Species of the Genus Arctium L.

Abstract: The review summarizes information from the literature on the distribution, study of the composition and biological activity of metabolites, total extracts of plants of the genus Arctium L. of the world flora. In Russia, the roots of three species are allowed to be harvested and used: A. lappa, A. tomentosum, A. minus. To date, the most studied composition of metabolites and pharmacological properties of great burdock. The chemical composition of A. atlanticum, A. debrayi, A. leiobardanum, A. neumani, A. platyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Mercury was not found in the studied objects. This indicates the safety of the studied roots and rhizomes [6].…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Mercury was not found in the studied objects. This indicates the safety of the studied roots and rhizomes [6].…”
Section: Resultsmentioning
confidence: 52%
“…During field research in RNO-Alania, the presence of commercial thickets of elecampane (Inula helenium L.), greater burdock (Arctium lappa L.), and dandelion (Taraxacum officianale Wigg.) was established [6]. In this connection, it seemed relevant to study their chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…The BAS components dominating in different parts of big burdock ensure in pharmacological effect of this species. 44,56,58,59 As a result of microscopic examination it was found that in the leaves such group as anthocyanins is present. The maximum absorption in the visible area of the spectrum of the acidified aqueous extract of the leaf petiole is well pronounced, it is located in the long-wavelength region of the spectrum, where only coloured compounds are absorbed in the wavelength range peculiar for individual anthocyanins.…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemical analysis of the extract and fractions revealed the presence of such groups of biologically active substances (BAS) as flavonoids, phenolic acids, tannins, polysaccharides, saponins, terpenoids (Table 1) which confirms the data given in the topic-related sources on chemical composition of burdock. [56][57][58][59][60] The predominant group in leaves and fructus are phenolic compounds (flavonoids, phenolic acids, tannins), polysaccharides. The BAS components dominating in different parts of big burdock ensure in pharmacological effect of this species.…”
Section: Discussionmentioning
confidence: 99%
“…In the period from 2011 to 2015 conducted a study of the effect obtained from the roots and rhizomes of additives on the technological process and the quality of bread, using the physicochemical methods described in the manual [6][7][8]. Microbiological evaluation of products was carried out in accordance with the requirements of SanPiN 2.3.2.1078, TR TS 021/2011 [9][10][11][12].…”
Section: Methodsmentioning
confidence: 99%